Im Hochsommer der Kunst 1890-1925 : Portrait einer Epoche aus Steirischen Sammlungen. - Neue Galerie am Landesmuseum Joanneum, Graz; Blaha, Julia; Dimitrion, Sokratis; Fenz, Werner; Holler, Christiane; Kaiser, Barbara; Marko, Eva; Schaukal, Barbara; Steinle, Christa; Weibel, Peter (Graz : Neue Galerie am Landesmuseum Joanneum, 1997)
Ambrosi, Gustinus ; Andri, Ferdinand ; Baselli, Marie von ; Blauensteiner, Leopold ; Boeckl, Herbert ; Böhler, Hans ; Brandstetter, Hans ; Bresslern-Roth, Norbertine von ; Brosch, Klemens ; Coltelli, Elfriede von ; Darnaut, Hugo ; Diefenbach, Karl Wilhelm ; Dobrowsky, Josef ; Egger-Lienz, Albin ; Egner, Marie ; Eisenschitz, Willy ; Fohn, Emanuel ; Fossel, Marta Elisabet ; Gerstl, Richard ; Gollob, Heinrich ; Gösser, Wilhelm ; Granner-Milles, Olga ; Grimm, Leo ; Guttenberg, Rosa von ; Hallavanya, Emilie von ; Hammerschlag, Margarethe ; Hanak, Anton ; Hiessleitner-Singer, Emmy ; Hoffmann, Josef ; Hölzel, Adolf ; Holzhausen, Olga Freifrau von ; Hotter, Alwine ; Jettmar, Rudolf ; Jungel, Ernst Reno ; Jungnickel, Ludwig Heinrich ; Kara, Mihaly ; Kasimir, Luigi ; Kasimir-Oeltjen, Elsa ; Kirchsberg, Ernestine von ; Klemencic, Igo ; Klemm, Walter ; Klenk, Eduard ; Klimt, Gustav ; Klinger, Max ; Koch-Langentreu, Friederike ; Köck, Franz ; Kokoschka, Oskar ; Kolig, Anton ; Koller-Pinell, Broncia ; Kraus, Felix ; Krönig, Hedwig ; Kurtz, Camilio ; Kurzwell, Maximilian ; Lang, Erwin ; Larsen, Oskar ; Laske, Oskar ; Lauzil, Cora ; Ledenig, Adolf ; Leskoschek, Axl ; List, Wilhelm ; Löffler, Berthold ; Mader, Karl ; Marussig, Anton ; Mediz-Pelikan, Emilie ; Michalek, Ludwig ; Moll, Carl ; Moser, Kolo ; Town, Carl O'Lynch of ; Oppenheimer, Max ; Passini, Rita ; Pauluzzi, Daniel ; Paungarten, Emmy von ; Presuhn, Ludwig ; Putz, Leo ; Rantz, Anton ; Reichel, Carl Anton ; Roux, Oswald ; Schaukal, Wolfgang von ; Scheu, Leo ; Schiele, Egon ; Schmidtbauer, Paul ; Schulda, Carl ; Silberbauer, Fritz ; Sterrer, Karl ; Stöhr, Ernst ; Stoitzner, Josef ; Stolba, Leopold ; Stössel, Oskar ; Stuck, Franz von ; Stundl, Theodor ; Teschner, Richard ; Thoma, Emil ; Thöny, Wilhelm ; etc.
Im Hochsommer der Kunst 1890-1925 : Portrait einer Epoche aus Steirischen Sammlungen, Neue Galerie am Landesmuseum Joanneum, Graz, 11. Juni bis 2. November 1997
biografie
Duits
boek
Keywords: begin 20ste eeuw; Wenen